Backlash or reinforcement? Donald Trump’s 2017 inauguration and shifting climate beliefs in the United States - Yidan Sun; Ke Shen; Mayank Kejriwal (npj Climate Action)
Abstract Efforts to counter climate change skepticism have become a key sociopolitical issue. Researchers increasingly recognize the role of “elite cues” from political leaders in shaping climate attitudes; yet quantitative analysis of specific recent events, such as President Trump’s 2017 inauguration, remains limited. Through two research objectives, this study examines whether Trump’s first inauguration modified the association between political identity (Democrat, Republican, and Independent) and overall climate change beliefs among Americans, and whether it influenced support or opposition for specific environmental policies, such as fracking and nuclear energy. Multinomial regression models, controlled for socio-demographic variables, reveal significant changes in association, as well as a potential “backlash effect”: the administration’s anti-climate stance appeared to strengthen pro-climate beliefs among Democrats and Independents, while Republicans’ beliefs remained largely unchanged. The study’s findings invite a more complex interpretation, compared to earlier literature, of the impacts of political cues on climate skepticism today.